Improvement of production facilities for improving the sales of banana crafts managers and improving production facilities for improving the sales of banana crafts and peek crafts - Yahya, Idhar; Siregar, Khawarita (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The business of making chips has two main products namely peyek chips and banana chips. Making peyek chips and banana chips is done manually using a very simple production facility. The process of frying chips requires a long time because the craftsman only has 1 stove and 1 pan so that the frying process is carried out alternately between peyek and banana chips. This has an impact on a limited quantity of projects so that often customer requests cannot be fulfilled. The quality of chips produced sometimes does not satisfy consumers because it is not crispy if stored for a period of time. This is because the crafters use thin plastic and the process of adhesion to the packaging activities is carried out using candles and kerosene lamps. In addition to not sticking to plastic, there is also a hollow plastic package so that air can get into the chips. The dedication team provided solutions to increase production in the form of 2 units of high pressure cookers, 1 unit of furnace, 3 units of iron frying pan, 1 unit of plastic packaging adhesive (sealer), 1 unit of mechanical sweet potato slicer, 1 unit of semi-mechanical banana slicer, procurement brands and thick plastic. Utilization of these production facilities results in the addition of the types of products produced, namely tojin beans, sweet potato chips, pan flowers and rengginang. Increasing the quality and quantity of products has an impact on increasing the market so that it has been marketed to simple housing, medium housing complexes and now modern outlets are willing to accept the products produced.